The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5505/ejm.2019.10337
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Post-Traumatic Stress Disorder Following Unintentional Injuries in Children

Abstract: Post-traumatic stress disorder (PTSD) is a trauma and stressor-related disorder that might have prominent negative effects on the social and academic life of children. Unintentional injuries are the leading reason for physical disability and death during childhood. We aimed to investigate PTSD symptoms in children withunintentional injuries who weretreated in hospital. Children who were injured due to various causes and treated in emergency servicewere retrospectively evaluated for PTSD symptoms. The PTSD symp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…But similar to our findings, another study conducted during the COVID-19 pandemic has also shown that healthcare professionals and the other part of the society are similarly affected by the pandemic (Pappa et al, 2020). In addition, people who have been exposed to traumatic experiences or adverse experiences can be affected at different levels in relation to factors such as their proximity to the event and the severity of traumatic events (Iz et al, 2019;Lai et al, 2020;May & Wisco, 2016). Previous research indicated that those who struggle in the front line with the first responders are exposed to a more intense stress load (Tatebe et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…But similar to our findings, another study conducted during the COVID-19 pandemic has also shown that healthcare professionals and the other part of the society are similarly affected by the pandemic (Pappa et al, 2020). In addition, people who have been exposed to traumatic experiences or adverse experiences can be affected at different levels in relation to factors such as their proximity to the event and the severity of traumatic events (Iz et al, 2019;Lai et al, 2020;May & Wisco, 2016). Previous research indicated that those who struggle in the front line with the first responders are exposed to a more intense stress load (Tatebe et al, 2020).…”
Section: Discussionsupporting
confidence: 88%
“…The CRIES-8 is a brief child-friendly measure widely used as a screening tool to measure children at risk for post-traumatic stress symptoms (Perrin et al 2005). The validity and reliability study of the scale was previously conducted (Şahin et al 2007) and later revised by Iz et al (Iz et al 2019). It is an 8-item self-report measure that has been applied in a variety of cultures to assess posttraumatic stress symptoms in children.…”
Section: Children's Impact Of Event Scale (Cries-8)mentioning
confidence: 99%
“…The Children's Impact of Event Scale (CRIES-8) is a screening test ideated by Perrin et al 13 and subsequently validated and revised by Sahin et al 14 and by Iz et al 15 to identify children at risk to develop post-traumatic stress disorders. It included 8 items investigating about posttraumatic stress symptoms in children, and in our study, its questions were adapted to the ongoing COVID-19 pandemic.…”
Section: Methodsmentioning
confidence: 99%